A Problem Concerning Yamabe-Type Operators of Negative Admissible Metrics. (10th May 2012) - Liang, Jin; Zhu, Huan
Abstract : This paper is about a problem concerning nonlinear Yamabe-type operators of negative admissible metrics. We first give a result onσ k Yamabe problem of negative admissible metrics by virtue of the degree theory in nonlinear functional analysis and the maximum principle and then establish an existence and uniqueness theorem for the solutions to the problem.